Toward equitable interventions in public mental health: a rview - Reininghaus, Ulrich; Reinhold, Annika S.; Priebe, Stefan; Rauschenberg, Christian; Fleck, Leonie; Schick, Anita; Schirmbeck, Frederike; Myin-Germeys, Inez; Morgan, Craig; Hartmann, Jessica A. (JAMA psychiatry, 2024)
The field of public mental health is evolving to tackle the profound impact of global challenges such as climate change, migration, and health crises. These issues accentuate health and social inequities, necessitating a focus on how to achieve interventions that are equitable and enhance mental health across all societal strata.Population-based interventions can inadvertently exacerbate mental health inequities if they are primarily assessed by, and beneficial to, the most advantaged. Dimensional approaches such as the Hierarchical Taxonomy of Psychopathology offer a more nuanced understanding of mental health, capturing the whole spectrum of symptom severity in a culturally sensitive and less stigmatizing way. In addition, adopting intersectional, participatory, and settings-based approaches can help tailor interventions to the unique needs of marginalized groups.In moving toward more equitable interventions in public mental health, it is imperative to adopt an approach that integrates multiple frameworks to address the complexity of mental health inequities. At the core of this integrated approach is the recognition that mental health exists on a continuum. Intersectionality theory can help to identify the root (fundamental) causes of mental health while participatory and settings-based approaches ensure that interventions are relevant, culturally sensitive, and accessible to all. By adopting these approaches, interventions that are not only effective in “shifting the curve” toward better mental health, but are also equitable in their reach and impact, can be developed.
Gesehen am 17.04.2025